Bioactivity of five invasive weed extracts against the fall armyworm pest (Spodoptera frugiperda) - SILVI IKAWATI; MUHAMMAD CHEN CHEN; NUR AVIVA; DIMAS AGUNG AHMADJATI; DUROTUN NADHIFAH; SYIFA KAMILA ANISA DARMAWAN; FERY ABDUL CHOLIQ (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ikawati S, Chen MC, Aviva N, Ahmadjati DA, Nadhifah D, Darmawan SKA, Choliq FA. 2026. Bioactivity of five invasive weed extracts against the fall armyworm pest (Spodoptera frugiperda). Biodiversitas 27 (3): d270310. https://doi.org/10.13057/biodiv/d270310. Spodoptera frugiperda (Lepidoptera: Noctuidae) or Fall Armyworm (FAW) is an invasive pest that attacks corn plants. Synthetic insecticides are commonly used for pest control but are not environmentally friendly, prompting the need for alternatives such as botanical insecticides. Sleeping grass (Mimosa pudica), nutgrass (Cyperus rotundus), Bermuda grass (Cynodon dactylon), wild sage (Lantana camara), and goatweed (Ageratum conyzoides) are invasive weeds in agroecosystems that have the potential to be used as botanical insecticides. This study aims to determine the bioactivity of the invasive weed extracts against FAW. Methods using bioassay in the laboratory. For each type of weed extract, an experiment was carried out with five levels of extract concentration (each extract using a different range) and two controls, which were repeated four times with ten individual 3rd instar larvae of FAW per repetition. The results showed that five invasive weed extracts have the potential to be used as insecticides, caused an increase in larval mortality (>70%), decreased the feeding activity (>50%), caused weight reduction (>50%), and reduced the percentage of successful development of pupae and adults (<15%). The LC50 values from the smallest to highest at 144 h after application were for C. dactylon aerial parts extract (6%), C. rotundus tuber extract (16%), A. conyzoides leaf extract (22%), L. camara leaf extract (49%), and M. pudica leaf extract (53%). For LT50 of M. pudica at a concentration of 70%, C. rotundus at a concentration of 50%, C. dactylon at a concentration 29%, L. camara at a concentration of 60%, and A. conyzoides at a concentration of 41% were 90, 57, 73, 81, and 42 h, respectively.